Perancangan Corporate Identity Sebagai Media Promosi Untuk Museum Panji - didit prasetyo nugroho (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2019)
The story of Panji is a native culture of Javanese society that has spread to foreign countries. The human values in the Panji stories are an integral part of Javanese culture. The Panji Museum which is a place to preserve and maintain that the Panji culture is not lost to the times will soon be ready to be opened to the general public. However, the Panji Museum currently does not have a visual identity to introduce and promote its existence. The purpose of this study was to design a visual identity design from Panji Museum in the form of corporate identity as a promotional medium. It is hoped that this research can produce corporate identity designs in the form of logos, museum catalogs, museum merchandise, posters and booklets that are in accordance with the characteristics of the Panji Museum.